Some Effects of Subsea Water Pipeline Construction on Sessile Benthic Community Structure of Redang Island, Malaysia - Rezai-Marnani, Hamid (1998)
A pipeline system, constructed in 1997- 1998, to provide water to Redang Island, traverses an area covered with coral reefs. Biological studies were conducted before and following the construction to monitor changes in habitat and biota at selected sites. Pre-construction studies consisted of conducting inventories of predominant marine life, and evaluating sites for their sensitivity to construction, whilst, post-construction studies involved assessment of d isturbed areas and monitoring the pattern of re-colonization by marine life. Marine environmental impact associated with the pipeline-crossing was monitored in the vicinity of the Island for one year. Evidence of the pipeline impact was assessed mainly by values concerning the abundance of zoobenthic community (including corals) and species diversity indices. Annelids and Arthropods were the most dominant phyla numerically during both study periods, being greater in pre-construction period. Student t-test and One-way ANOVA analyses revealed that there was no significant differences between total abundance of sessile macroinvertebrates during pre and post-construction periods. Student t-test revealed a significant difference between the means of live coral coverage during pre and post-construction periods. There was no apparent change in total number of macro-invertebrates as a result of pipe line construct ion. Results indicated that impacts arising from marine-crossing were short-term and non-residual.